2007
DOI: 10.1038/sj.ejcn.1602758
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in the estimation of food servings against the portions in food photographs

Abstract: Objective: In diet surveys, quantitative underestimation of food consumption may be due to intentional misreporting or false portion-size reporting. Perception of food photographs used as aids for assessing the actual amounts may have an effect. This study was carried out to assess the validity of food photographs. Design: A real-time test protocol where 52 presented food servings were compared against photographed portions with similar food items. Subjects: Volunteers from the Rehabilitation Company Petrea (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
142
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 19 publications
(53 reference statements)
14
142
7
1
Order By: Relevance
“…Some studies have evaluated the errors related to perception of foods in photographs while assessing the portion of foods presented to the participant (3,(6)(7)(8)13,14) . They speculate that assessment of portion size would not be biased by factors such as participants' unwillingness to divulge what they have eaten (1,15) .…”
mentioning
confidence: 99%
“…Some studies have evaluated the errors related to perception of foods in photographs while assessing the portion of foods presented to the participant (3,(6)(7)(8)13,14) . They speculate that assessment of portion size would not be biased by factors such as participants' unwillingness to divulge what they have eaten (1,15) .…”
mentioning
confidence: 99%
“…The following calculations have not been adjusted for energy-under-reporting, and should therefore be interpreted with due care. However, it is noteworthy that social desirability may also lead to over-reporting of foods perceived to be healthy, including horticultural crops, among some groups (14,15) . The UK and USA have diverse diets compared to most countries.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…A photographic booklet is convenient compared with three-dimensional models for example, since it is easy for the interviewer to carry and can include a wide range of different types of foods. In high-income countries, the validity of using food photographs in portion size estimation has been studied in different age groups, including adults (5)(6)(7)(8)(9) , adults and elderly persons (10) and children and adolescents (7,11,12) . The study designs have varied from studies in which the subjects serve themselves a variety of foods in portions of their choice and the next day they are asked to recall the food items and estimate their amounts (5) to studies in which the food is not eaten but shown to the subject and the assessment of portion size is done simultaneously (9) .…”
mentioning
confidence: 99%
“…In high-income countries, the validity of using food photographs in portion size estimation has been studied in different age groups, including adults (5)(6)(7)(8)(9) , adults and elderly persons (10) and children and adolescents (7,11,12) . The study designs have varied from studies in which the subjects serve themselves a variety of foods in portions of their choice and the next day they are asked to recall the food items and estimate their amounts (5) to studies in which the food is not eaten but shown to the subject and the assessment of portion size is done simultaneously (9) . In general, despite the fact that there is large variation in individuals' ability to estimate portion sizes (7)(8)(9)(10)(11)(12) , many studies have shown acceptable results on the group level (6,(8)(9)(10)(11)(12) and the use of food photographs has become an established practice in dietary studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation